Top-down systemic challenges to current Paralympic pathways - Patatas, J.M.; De Bosscher, V.; Van Neutegem, A. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
Effective elite sport policies will influence the development of successful elite athlete pathways, however, the Paralympic sport system and athletes with an impairment have been underexplored. In this chapter, we review the wide range of factors that directly impact Paralympic pathways development from a sport policy perspective. In doing so, we use the sports policy literature as a guide to identify the policy-related challenges to current Paralympic pathways. We conclude that policymakers` knowledge of Para sport influences the way the policy agenda that contours Paralympic pathways is developed. Taken together, the way Para sport policies are shaped and implemented requires a holistic, flexible, and context-specific approach.